THE DEVELOPMENT OF AUDIO VISUAL LEARNING MEDIA YOUTUBE VIDEO OF HINDU-BUDDHIST SITES IN BANYUWANGI TOWARDS HISTORY LEARNING IN GRADE X OF HIGH SCHOOL - Elya Sintya; Mohamad Na'im; Rully Putri Nirmala Puji (History Education, University of Jember, 2019)
History learning requires learning media to facilitate understanding of events and historical heritage. Youtube video audio visual learning media is a medium that is able to present images and videos to assits students understanding historical material. Banyuwangi Hindu-Buddhist sites were selected as material in development. The purpose of this study is to generate learning media which is adequated and validated, and to produce effective learning media to be enganged in historical learning. This study utilized Borg and Gall model which comprises of seven development stages, namely: (1) Research and information collection, (2) Planning, (3) Develop preminary form of product, (4) Preliminary field testing, (5) Main product revision, (6) Main Field Testing, and (7) Operational Product Revision. The obtained product has been validated by content material expert, media and design expert. The content validation value obtained 93,3% means as